The discrepancy between preoperative cervical sagittal vertical axis and T1 slope predisposes inferior clinical outcomes in patients with cervical spondylotic myelopathy after cervical laminoplasty - Wang, Dong-Fan; Zhu, Wei-Guo; Wang, Wei; Li, Xiang-Yu; Kong, Chao; Liu, Cheng-Xin; Shi, Bin; Lu, Shi-Bao (Frontiers in Surgery, 2022)
Objective: Cervical sagittal parameters have been widely used to predict clinical outcomes in patients with cervical spondylotic myelopathy (CSM). This study aims to coin a novel cervical sagittal parameter defined as the ratio of cervical sagittal vertical axis to T1 slope (CSVA/T1S) and to investigate the correlation between CSVA/T1S and postoperative HRQOL after laminoplasty. Methods: A total of 102 CSM patients treated with cervical laminoplasty from our database were retrospectively reviewed. All patients were followed up for > 12 months. Radiological parameters were measured using lateral cervical radiographs, including occiput-C2 lordosis (OC2), cervical lordosis (CL), CSVA, and T1S. Clinical parameters included the Japanese Orthopedic Association (JOA) score, neck disability index (NDI), and JOA recovery rate. Patients were grouped by preoperative T1S, T1S-CL, and CSVA/T1S value, respectively. Clinical and radiological outcomes were compared between the groups. Results: Patients with high CSVA/T1S had greater OC2 and CSVA but lower CL than those in the low CSVA/T1S group pre-and postoperatively. With respect to HRQOL results, the final NDI was 12.46 ± 9.11% in the low CSVA/T1S group, which was significantly lower than that in the high CSVA/T1S group (17.68 ± 8.81%, P = 0.040). Moreover, only CSVA/T1S was detected to be significantly correlated with final NDI (r = 0.310, P = 0.027). No significant correlation was found between clinical results and other cervical sagittal parameters, including T1S, CSVA, and T1S-CL. Conclusions: Preoperative CSVA/T1S was correlated with postoperative NDI in patients with CSM after cervical laminoplasty. Patients with low preoperative CSVA/T1S achieved better neurological function improvement after cervical laminoplasty. Cervical laminoplasty could be an appropriate choice for patients with lower preoperative CSVA/T1S.